One dimensional hierarchical nanoflakes with nickel-immobilization for high performance catalysis and histidine-rich protein adsorption. Issue 30 (4th July 2019) - Wang, Na; Wen, Qiong; Liu, Libin; Xu, Jingli; Zheng, Jing; Yue, Mingbo; Asiri, Abdullah M.; Marwani, Hadi M.; Zhang, Min
Abstract : Herein, we described a facile strategy for the controllable synthesis of three dimensional hierarchical nickel based composites, which exhibited excellent performance on catalysis and protein adsorption. Abstract : Complex hierarchical structures are closely associated with their performance in catalysts and protein adsorbents. However, it still remains a great challenge to develop a facile strategy to engineer their structural traits. Herein, we describe a facile strategy combining a hydrothermal reaction and mussel chemistry with a subsequent thermal treatment process for the controllable synthesis of three dimensional hierarchical nickel based composites, which are constructed from MnO nanowire (NW) cores and thin Al2O3@C shells anchored with ultrasmall metallic Ni nanoparticles (NPs). During the processing, MnO2 NWs were utilized as templates for the cores, while the two dimensional NiAl nanosheets were directly adopted as the shell to form three dimensional hierarchical MnO2 @NiAl nanowires. After coating with polydopamine-Ni 2+ (PDA-Ni 2+ ) and subsequent carbonization under a nitrogen atmosphere, high coverage of metallic Ni NPs and the transformation from MnO2 to MnO cores were all observed in the final product. The size of outer Ni NPs and the morphology of the carbonized product can be tailored by varying the temperature of carbonization, which is also in close association with the performance of catalysis and protein adsorption. Notably, the N-doped carbon layer from polydopamine can act as an electron conductor and facilitate the prevention of the migration and aggregation of the Ni nanoparticles, while the ultrafine Ni nanoparticles can achieve maximum material utilization for catalysis and protein adsorption. In addition, the unique structures can expose more active catalytic or adsorption sites while enabling free diffusion of mass/electron transfer. As a result, the MnO@Al2 O3 @C/Ni composite exhibited excellent performance in catalysis and protein adsorption.